2015
DOI: 10.1007/s11999-015-4414-7
|View full text |Cite
|
Sign up to set email alerts
|

Do Oxidized Zirconium Femoral Heads Reduce Polyethylene Wear in Cemented THAs? A Blinded Randomized Clinical Trial

Abstract: Background Charnley low-friction torque total hip arthroplasty (THA) remains the gold standard in THA. The main cause for failure is wear of the socket. Highly crosslinked polyethylene (HXLPE) has been associated with reduced wear rates. Also, oxidized zirconium has shown in vitro reduced wear rates. However, to our knowledge, there are no data comparing oxidized zirconium femoral heads with metal heads against HXLPE or ultrahigh-molecular-weight polyethylene (UHMWPE) when 22.25-mm bearings were used, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…However, Zaoui et al at 4 years follow-up did find a significant reduction (p < 0.001) in wear rate with OxZr (0.02 mm/year) over CoCr (0.05 mm/year) against highly crosslinked polyethylene in all-poly cups (Smith & Nephew Reflection) using the Martell method. 21 Wear may not be the most important long-term issue in modern highly crosslinked polyethylene bearings for total hip arthroplasty. Corrosion at the head-neck junction of the femoral components may be a clinical problem limiting the longevity of these implants.…”
Section: Discussionmentioning
confidence: 99%
“…However, Zaoui et al at 4 years follow-up did find a significant reduction (p < 0.001) in wear rate with OxZr (0.02 mm/year) over CoCr (0.05 mm/year) against highly crosslinked polyethylene in all-poly cups (Smith & Nephew Reflection) using the Martell method. 21 Wear may not be the most important long-term issue in modern highly crosslinked polyethylene bearings for total hip arthroplasty. Corrosion at the head-neck junction of the femoral components may be a clinical problem limiting the longevity of these implants.…”
Section: Discussionmentioning
confidence: 99%
“…7,26 Proponents of the use of OxZr claim that it leads to a reduced wear rate when compared with metal femoral heads, but a similar wear rate when compared with ceramic alternatives. 15,18,21 As THA is performed in a progressively younger patient population, there is a higher emphasis placed on differences in revision rates and PE wear with the various component options. Further work needs to evaluate the longterm outcomes comparing OxZr femoral heads with other bearing surface combinations in THA.…”
Section: Discussionmentioning
confidence: 99%
“…Zaoui et al and Kadar et al reported no revisions in their cohorts with 2-and 6-year follow-up, respectively. 15,17 Morison et al illustrated a Kaplan-Meier curve demonstrating a 94.1% (CI or confidence interval 91.5-96.6%) cumulative survival at 8 years, with no significant difference between any of their studied bearing surface combinations (CoCr/OxZr vs. UHMWPE/XLPE or silane cross-linked polyethylene). 18 This study alongside Jassim et al and Jonsson et al showed revisions were only secondary to infection and recurrent dislocation among the studies ultimately included in this systematic review.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of a fatigue-resistant substrate underneath an oxidized, ceramicized surface was designed to emulate superior wear and scratch properties of ceramics while minimizing the risk for brittle fracturing [16] , [17] . This novel design has translated clinically to midterm in vivo studies demonstrating reduced linear and volumetric wear of polyethylene (PE) liners when compared with cobalt-chromium (CoCr), ceramic, and steel femoral heads [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%